(untitled) (Research, Society and Development, 2022)
In this research, the changes in the rheological behavior and in the electromagnetic shielding of commercial acrylic paint modified with xanthan gum (GX) and conductive carbon black were evaluated. The factorial design methodology of experiments was used in two experimental levels for GX and carbon black for optimization of the study. The Herschel-Bulkley rheological model was used to determine the main rheological parameters. GX exerted greater influence on the yield strength (t0) in relation to carbon black. Variations in t0 values were 1000% between the studied formulations. Electromagnetic shielding results confirmed better dispersion of carbon black in formulations with low concentrations of xanthan gum. The additive inks increase the activation energy and the constants C1 and C2 of the WLF law for the time-temperature superposition test. The thixotropy test, carried out using the methodology of three strain intervals, corroborates the values obtained for the ultimate yield stress. The paint restructuring is more pronounced at low GX concentration.